KONSTRUKSI SOSIAL SUKU BAJO DALAM MELESTARIKAN BUDAYA DAN EKOSISTEM KELAUTAN BAJOE KABUPATEN BONE - Afdal Afdal (xxxx-xxxx, 2026)
The social construction of the Bajo tribe in preserving marine culture and ecosystems in Bajoe, Bone Regency, South Sulawesi. Thesis, Social Sciences Education Study Program, Makassar State University (supervised by Dr. Ahmadin, S.Pd., M.Pd. and Shasliani, S.Pd., M.Pd.).This study aims to determine: 1) the Bajo people's understanding of their marine culture and traditions, 2) analyze the forms of social construction in preserving marine culture and ecosystems in the Bajo region, 3) identify the challenges and threats faced in preserving marine culture and the environment. The data collection technique used was a qualitative approach with a case study method. Data were collected through observation, in-depth interviews, and documentation.The results show that: 1) the Bajo people have a strong understanding of ancestral cultural values and marine traditions, especially among the older generation, but this is beginning to shift among the younger generation; 2) the Bajo people preserve the ecosystem through traditional methods, such as not using destructive fishing gear and protecting marine areas considered sacred; 3) The challenges faced include the current of modernization, declining participation of the younger generation, and environmental damage due to external activities. This research shows that the social construction of the Bajo community remains a crucial force in maintaining their cultural identity and the sustainability of the marine ecosystem that is central to their lives.